Unity and Diversity in the Carolingian Church - McKitterick, Rosamond (Studies in church history, 1996)
With their steady series of conquests during the eighth century, adding Alemannia, Frisia, Aquitaine, the Lombard kingdom in northern Italy, Septimania, Bavaria, Saxony, and Brittany to the Frankish heartlands in Gaul, the Carolingians created what Ganshof regarded as an unwieldy empire. Was the Carolingian Church unwieldy too? Recent work, notably that of Janet Nelson, has underlined not only the political ideologies that helped to hold the Frankish realms together, but also the practical institutions and actions of individuals in government and administration. Can the same be done for the Church? Despite the extraordinary diversity of the Carolingian world and its ecclesiastical traditions, can it be described as a unity? What sense of a ‘Frankish Church’ or of ‘Frankish ecclesiastical institutions’ can be detected in the sources?